PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT VICTORY CHINGLUH INDONESIA DI KABUPATEN TANGERANG - Deandra Sasi Raya Mahardika; Eko Trianto; Bambang Mardisentosa (LPPM Politeknik Pratama, 2025)
This study aims to analyze the effect of leadership style, motivation, and work environment on employee performance at PT Victory Chingluh Indonesia, Tangerang Regency. Using a quantitative approach and survey method, primary data was collected through a Likert scale questionnaire from 100 respondents selected by random sampling. Data analysis was performed using SPSS 25, which included validity and reliability tests, classical assumptions, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results showed that partially, leadership style (t-count 2.362 > t-table 1.984), motivation (t-count 2.864 > t-table 1.984), and work environment (t-count 5.301 > t-table 1.984) each have a positive and significant effect on employee performance at a significance level of < 0.05. Additionally, the F test results indicate that simultaneously, the three independent variables also have a significant effect on employee performance (Fcount 24.008 > Ftable 2.699) with a significance level of 0.000. Thus, it can be concluded that leadership style, motivation, and work environment are important factors that influence employee performance in the company.